First Record of Bursatella Leachii Blainville, 1817(Mollusca, Opisthobranchia, Aplysiidae) in the Syrian waters. - زيني, أديب; صقر, فائز; موسى, امتثال (Latakia University Journal -Biological Sciences Series, 2022)
Sea hares are benthic mollusks, spread in warm, temperate and tropical waters all over the world. Eight individuals of the species Bursatella Leachii Blainville, 1817 (Mollusca, Opisthobranchia, Aplysiidae), and one individual of the species Goniobranchus annulata, Eliot, 1904 (Mollusca: Opistobranchia: Chromodorididae) were collected from the Syrian marine waters (Jableh city) during a comprehensive survey of the biocenosis community associated with Eriphidae crabs on the shallow rocky bottom during the period from 30 March to 20 June 2021.